Application of RAPP Method in Service Relationship Marketing with a Special Focus on Environmental Aspects - Ewa KORELESKA (Communications of International Proceedings, 2020)
The aim of this study is to present the possibilities of using the RAPP model in service relationship marketing. The subject of the study are catering outlets located on premises of Bydgoszcz universities. The research hypothesis assumes that students’ expectations from catering outlets and the remaining elements of marketing, as set out in the RAPP model, are not fully met. Moreover, it is assumed that there is no significant link between the students’ gender and their preferences concerning introduction of organic products into the offer of catering outlets. The survey was carried out in 2019 and 2020, and was divided into a few stages. Data collection methods such as a direct survey, group interviews and observations. The data was analyzed with the use of mathematical statistical methods. The survey results show that students’ expectations from the offer of catering outlets situated on premises of the universities in Bydgoszcz are not fully met, especially in terms of ‘Relations’, and ‘Arena of Presentation’. The element of marketing referred to as ‘People’ was the best rated. Moreover, no significant relation between the gender of students and their preferences regarding introduction of organic products into the offer of catering outlets was found. This confirms the research hypothesis. Summing up, it needs to be noted that the RAPP method proved to be useful in the survey, as it highlighted weaknesses and strengths of canteens functioning in Bydgoszcz universities, indicating the direction of changes to be followed by entrepreneurs in service marketing management.
Keywords: Marketing; Management; Healthier Lifestyle; Model RAPP; Service Relationship Marketing; Marketing Mix; Universities; Organic Food; Internet; Services Gastronomic.